Pulsed Electric Fields-Assisted Extraction of Valuable Compounds From Arthrospira Platensis: Effect of Pulse Polarity and Mild Heating - Carullo, Daniele; Pataro, Gianpiero; Donsì, Francesco; Ferrari, Giovanna (Frontiers in Bioengineering and Biotechnology, 2020)
The present study aimed to investigate the effect of the main pulsed electric field (PEF) process parameters on the cell damages of A. platensis microalgae and the extractability of valuable compounds (water-soluble proteins (WSP), C-phycocyanin (C-PC), and carbohydrates (CH)). Aqueous microalgae suspensions (2%, w/w) were PEF-treated at variable field strength (E = 10, 20, 30 kV/cm), total specific energy (WT = 20, 60, 100 kJ/kgsusp), and inlet temperature (25, 35, 45°C), with either monopolar or bipolar square wave pulses (5 s of width, delay time between pulses of opposite polarities = 1, 5, 10, 20 s), prior to extraction with water at room temperature (25°C) for up to 3 h. High-pressure homogenization (HPH) treatment (P = 150 MPa, 3 passes) was used to achieve complete cell disruption to quantify the total extractable content of target intracellular compounds. Scanning electron microscopy (SEM) and optical microscopy analyses clearly showed that PEF merely electroporated the membranes of algae cell, without damaging the cell structure and forming cell debris. The application of PEF treatment (monopolar pulses, 20 kV/cm and 100 kJ/ kgsusp) at room temperature significantly enhanced the extraction yield of WSP (17.4% dry weight, (DW)), CH (10.1% DW), and C-PC (2.1% DW), in comparison with the untreated samples. Bipolar pulses appeared less effective than monopolar pulses and led to extraction yields dependent on the delay time. Additionally, regardless of pulse polarity, a clear synergistic effect of the combined PEF (20 kV/cm and 100 kJ/kgsusp)-temperature (35°C) treatment was detected, which enabled the extraction of up to 37.4% (w/w) of total WSP, 73.8% of total CH, and 73.7% of total C-PC. Remarkably, the PEF treatment enabled to obtain C-phycocyanin extract with higher purity than that obtained using HPH treatment. The results obtained in this work suggest that the application of PEF combined with mild heating could represent a suitable approach for the efficient recovery of water-soluble compounds microalgal biomass.